Phenotyping Chickpeas and Pigeonpeas for Adaptation to Drought - Upadhyaya, Hari Deo; Kashiwagi, J; Varshney, Rajeev K.; Gaur, PM; Saxena, KB; Krishnamurthy, L; Gowda, CLL; Pundir, RPS; Chaturvedi, SK; Basu, PS; Singh, IP (Frontiers in Physiology, 2012)
The chickpea and pigeonpea are protein rich grain legumes used for human consumption in many countries. Grain yield of these crops is low to moderate in the semi-arid tropics with large variation due to high GxE interaction. In the Indian subcontinent chickpea is grown in the post-rainy winter season on receding soil moisture, and in other countries during the cool and dry post winter or spring seasons. The pigeonpea is sown during rainy season which flowers and matures in postrainy season. The rainy months are hot and humid with diurnal temperature varying between 25-35oC (maximum) and 20-25oC (minimum) with an erratic rainfall. The available soil water during postrainy season is about 200-250 mm which is bare minimum to meet the normal evapotranspiration. Thus occurrence of drought is frequent and at varying degrees. To enhance productivity of these crops cultivars tolerant to drought need to be developed. ICRISAT conserves a large number of accessions of chickpea (>20,000) and pigeonpea (>15,000). However only a small proportion (<1%) has been used in crop improvement programs mainly due to non-availability of reliable information on traits of economic importance. To overcome this core and mini core collections (10% of core, 1% of entire collection) have been developed. Using the mini core approach, trait specific donor lines were identified for agronomic, quality and stress related traits in both crops. Composite collections were developed both in chickpea (3000 accessions) and pigeonpea (1000 accessions), genotyped using SSR markers and genotype based reference sets of 300 accessions selected for each crop. Screening methods for different drought tolerant traits such as early maturity (drought escape), large and deep root system, high water use efficiency, smaller leaflets, reduced canopy temperature, carbon isotope discrimination, high leaf chlorophyll content (drought avoidance) and breeding strategies for improving drought tolerance have been discussed.